2004
DOI: 10.1159/000079621
|View full text |Cite
|
Sign up to set email alerts
|

Caries-Inhibiting Effect of Preventive Measures during Orthodontic Treatment with Fixed Appliances

Abstract: A systematic review was performed of published data on the caries-inhibiting effect of preventive measures during orthodontic treatment with fixed appliances. The purpose was to develop evidence-based recommendations about the most effective means of preventing white spot lesions in orthodontic patients. The 15 studies included were divided into four groups based on comparable preventive measures: fluoride, chlorhexidine, sealants and bonding materials. The caries-inhibiting effect of the preventive measures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 33 publications
1
117
0
13
Order By: Relevance
“…1 This results in dissociation of calcium (Ca) and phosphate (PO 4 ) ions from enamel in an attempt to reach chemical equilibrium in the oral environment. 1,2 Thus, one possible inherent problem during the whole course of orthodontic treatment is the subsurface enamel demineralization around brackets, representing the primary phase of caries formation. 2 Prevalence of these acquired surface lesions due to orthodontic treatment, so-called white spot lesions (WSL), is relatively high, affecting more than 40% to 60% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 This results in dissociation of calcium (Ca) and phosphate (PO 4 ) ions from enamel in an attempt to reach chemical equilibrium in the oral environment. 1,2 Thus, one possible inherent problem during the whole course of orthodontic treatment is the subsurface enamel demineralization around brackets, representing the primary phase of caries formation. 2 Prevalence of these acquired surface lesions due to orthodontic treatment, so-called white spot lesions (WSL), is relatively high, affecting more than 40% to 60% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…El alto riesgo se atribuye a la presencia de diversos tipos de aparatos básicos y otros elementos auxiliares ortodóncicos que dificultan las medidas convencionales de higiene oral. 3,4 La literatura ha demostrado que los tratamientos de ortodoncia incrementan la acumulación de placa y la colonización bacteriana por lo que resultan afectados los tejidos periodontales y dentarios. [21][22][23][24][25] Si se permite el crecimiento de esta placa aparecerán algunos cambios cuyos resultados dan lugar al establecimiento de la gingivitis tras dos a tres semanas.…”
Section: Discussionunclassified
“…El alto riesgo es atribuido a la presencia de los alambres, arcos, ligaduras y otros elementos auxiliares ortodóncicos que dificultan las medidas convencionales de higiene oral. 3,4 Si se permite el crecimiento de la placa bacteriana sin interferencia de medidas de higiene oral, aparecerán algunos cambios cuyos resultados dan lugar al establecimiento de la gingivitis tras dos a tres semanas. En consecuencia, la prevención de la gingivitis, la forma inicial de la enfermedad periodontal, está ampliamente gobernada por la limitación del desarrollo de la placa bacteriana.…”
unclassified
“…Derks et al 24 concluded that the most effective means of preventing white spots is through the use of a high fluoride (1500-5000 ppm) gel and toothpaste used daily during orthodontic treatment. Another study indicated daily brushing with a fluoridated dentifrice along with daily rinsing with fluoride will help prevent demineralization.…”
Section: Discussionmentioning
confidence: 99%